Symbolic Meaning Analysis of Ciwaringin Batik Motifs on the Strengthening Project of the Pancasila Student Profile (P5) for Elementary School Students - Ayu Try Lestari; Nailah Tresnawati (STAI Miftahul Ula Nganjuk, 2024)
The international community has recognized batik as a cultural heritage originating from Indonesia through UNESCO. Batik represents a nation's culture with distinctive motifs that carry unique and symbolic meanings. The purpose of this research is to analyze the symbolic meanings of the Ciwaringin batik motifs in the context of the Strengthening the Profile of Pancasila Students (P5) Project in primary schools. The research method employed is qualitative descriptive to gain a profound understanding of the symbolic meanings of Ciwaringin batik in the context of the Pancasila Student Profile Strengthening Project (P5) in primary school students. The research objects consist of five Ciwaringin batik motifs: Pecutan, Yusufan, Tebu Sekeret, Gribigan, and Pring Sedapur. The findings indicate that the patented motifs such as Pecutan, Yusufan, Tebu Sekeret, Gribigan, and Pring Sedapur carry valuable lessons, teaching character education that includes faith and piety in the one and only God, noble morality, global diversity, mutual cooperation, independence, creativity, and critical thinking. These principles of character education can be applied in broader life and society.